MSME Dexterity Analysis: Absorptive Capacity and Knowledge Stickiness in Endemic Era of Depok MSME’s - Yanita Ella Nilla Chandra; Husnil Barry; Risya Zahrotul Firdaus; Titik Purwinarti; Ernita Dian Puspasari (University of Merdeka Malang, 2023)
This study aims to examine and investigate the effect of absorptive capacity on MSME’s agility, the effect of knowledge stickiness on the agility of MSME’s, and identify the key factors forming absorptive capacity and knowledge stickiness in MSME’s in Depok City. Testing the impact of MSME’s agility on economic resilience. Data were collected through a survey method with MSME’s in Depok City as the research population. The data analysis method using Partial Least Square (PLS). The study found that absorptive capacity had a significant negative effect on MSME’s agility, and knowledge stickiness had a significant positive effect on MSME’s agility. MSME’s agility is influenced by these two variables by 94.5% and the rest is influenced by other factors.